Disrupsi dan Penerimaan Kiai Kampung atas Media Sosial - Ridlwan, Mujib; Muhammad Khamid Lutfi; Ulya, Azimatul; Nur Fadhilah, Daniatun (Institut Agama Islam Al-Hikmah Tuban, 2022)
Abstract, This article examines the attitude of the village kiai (kiai kampung) towards the presence of a period of disruption, a period of rapid change in the social order. One of these changes was triggered by the presence of social media in society. This social media is not only forcing changes in the industrial world but also in pesantren and their caretakers, the kiai. Village kiai, who have been known as kiai who adhere to old culture and traditions, are currently experiencing a test with the presence of social media. This article tries to look at the attitude of the village kiai towards the presence of social media. The order of life that has been established for a long time, especially the order of the pesantren community, is being battered by the new order